Indonesian Students' Behavior Towards Decision-Making In Choosing Distance Learning (Study On Open And Distance Students) - Melisa Arisanty; Gunawan Wiradharma; Irla Yulia; Khaerul Anam; Dede Kurniyawan (Universitas Negeri Malang, 2023)
Abstract: The university needs to know what factors influence student behavior in determining distance learning. It is very necessary as a way to formulate an optimal marketing strategy. This study aimed to determine the influence of student behavior factors consisting of cultural, social, personal, and psychological factors in determining decisions to take distance learning at the Universitas Terbuka. This study's population was UT students registered in the 2023-1 semester, as many as 439,222 students. From this population, there were 10,119 students as respondents with quota sampling techniques from all branch offices throughout Indonesia and abroad. The data analysis technique used is Multiple Linear Analysis with the Enter Method and the SPSS 25.0 for Windows program. The results showed that the student's behavior strongly influenced their decisions in choosing a distance learning system. The main factors shaping student behavior in determining decisions to study remotely are social factors, such as social status and the role of students in society, as well as the personality factors of the students themselves, such as the personal decisions of students in understanding their needs for distance learning systems that are following the conditions they face. In addition to these two factors, cultural factors of residence and student psychology also shape student behavior in determining decisions to study remotely. By knowing these factors, it is hoped can continue to compete with other universities that also organize distance learning courses so that it is always expected to be the first choice of students to participate in the distance learning system.Keywords: Consumer Behavior, Purchasing Decisions, Distance Learning, Multiple Linear Analysis